Primary thyroid lymphoma with double expression of MYC and B-cell lymphoma-2 Gene (Indian Journal of Case Reports, 2021)
Primary lymphomas of the thyroid (PTLs) are rare entities. We report a case of high-grade B-cell lymphoma double hit (DH) of the thyroid gland with dual expression of MYC and BCL-2 gene in a 55-year-old woman. Most PTLs have a good prognosis to combined modality treatment but identification of DH lymphomas or double-expressor lymphomas is important as these are resistant to chemotherapy and radiotherapy and pose a challenge for the treatment of the same.